An Easy-to-Integrate Embedded Cascade Microspheres for Efficient Local Field Enhancement - Chen, Qiyu (Transactions on Engineering and Technology Research, 2024)
Surface-enhanced Raman spectroscopy (SERS) is a non-destructive and ultra-sensitive tool for optical trace detection. However, the complex manufacturing process hinders the application of SERS. For this reason, an embedded cascaded microsphere structure is proposed in this paper, which is easy to integrate and process. Such a structure is composed of large microspheres and small microspheres with micropores cascaded. More importantly, the micropore diameter at the bottom of the large microspheres is the same as that of the small microspheres. Through the finite element analysis, it is concluded that compared with a single microsphere, the photonic nanojet generated by this structure is stronger, which can achieve local electric field enhancement more effectively. Meanwhile, different materials of the cascade microspheres used in the embedded cascade have various reinforcement effects. In addition, compared with the manual physical alignment of two microspheres in the traditional cascade structure, this structure is easier to process and integrate, convenient for future integrated applications.